Lyrics of Sunshine and Shadow : the Tragic Courtship and Marriage of Paul Laurence Dunbar and Alice Ruth Moore. - Alexander, Eleanor (NYU Press, 2001)
A New York Times Notable Book of 2002!. Sexism, racism, self-hatred, and romantic love: all figure in prominently in this scholarly-but nicely hard-boiled-discussion of the bond between the famous Paul Laurence Dunbar and his wife Alice. Eleanor Alexander's analysis of turn-of-the-twentieth-century black marriage is required reading for every student of American, especially African-American, heterosexual relationships."--Nell Painter, Edwards Professor of American History, Princeton University, Author of Sojourner Truth, A Life, A Symbol. "Rich in documentation and generous in analy.